A Randomized Double-Blinded Dose-dependent Study of Metaraminol for Preventing Spinal-Induced Hypotension in Caesarean Delivery - Xiao, Fei; Xu, Wen-Ping; Yao, Han-Qing; Fan, Jia-Ming; Chen, Xin-Zhong (Frontiers in Pharmacology, 2021)
Purpose: Metaraminol has been suggested as one of the first line vasopressors for the prevention and treatment of hypotension during spinal anesthesia for Cesarean delivery. However, the optimal dose of prophylactic infusion of metaraminol remains unknown. Therefore, this study aimed to determine the median effective dose (ED50) and 90% effective dose (ED90) of weight-based fixed-rate metaraminol infusions for preventing spinal-anesthesia-induced hypotension in patients having combined spinal-epidural anesthesia for elective Caesarean delivery. Methods: One hundred and seventeen patients with singleton pregnancies were enrolled and randomly allocated into one of five groups in this study. Patients received prophylactic metaraminol infusion at a fixed rate of 0, 0.25, 1.0, 1.75 or 2.5 μg/kg/min in each group immediately after induction with intrathecal 10 mg of hyperbaric bupivacaine mixed with 5 μg of sufentanil. An effective prophylactic dose was defined as no occurrence of hypotension during the period of spinal introduction and neonatal delivery. Values for ED50 and ED90 of prophylactic infusion of metaraminol were calculated using probit regression. Characteristics of spinal anesthesia and side effects were recorded. Results: The ED50 and ED90 values of weight-based fixed rate of metaraminol infusion were 0.64 (95% CI, 0.04 to 1.00) μg/kg/min and 2.00 (95% CI, 1.58 to 2.95) μg/kg/min respectively. The incidence of hypotension decreased with an increased infusion rate of metaraminol in the five groups (test for trend, P <0.001). The incidence of hypotension was similar between group 0 and 0.25, but significant higher than other groups; the incidence of hypotension was also similar between group 1.0 and 1.75, but higher than group 2.5. The incidence of reactive hypertension was significantly higher in group 2.5 compared to the other groups. No difference was found in neonatal outcomes, including Apgar score and pH value of the umbilical artery. Conclusions: In summary, we have compared four different prophylactic weight-based infusion doses of metaraminol for preventing post-spinal hypotension in Cesarean delivery. The ED50 and ED90 values of metaraminol infusion for preventing spinal anesthesia-induced hypotension were 0.64 μg/kg/min and 2.00 μg/kg/min, respectively. This finding may be helpful for guiding clinical practice and further research.